2020
DOI: 10.3390/cancers12061373
|View full text |Cite
|
Sign up to set email alerts
|

Soluble PD-L1 in NSCLC Patients Treated with Checkpoint Inhibitors and Its Correlation with Metabolic Parameters

Abstract: We investigated the role of soluble PD-L1 (sPD-L1) in non-small cell lung carcinoma (NSCLC) patients treated with immune checkpoint inhibitors (ICI) and analyzed its association with clinical outcomes and metabolic parameters by 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT). Between July 2017 and May 2019, we enrolled 20 candidate patients of ICI therapy who had serum frozen samples and 18F-FDG PET/CT available, both at baseline and at the first response evaluation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…However, overall, the results are contrasted, and sPD-L1 alone does not appears as a sufficiently robust and reliable biomarker to predict outcome in most cases. In NSCLC, for example, some studies underlined that there is no difference in survival outcomes between low sPD-L1 and high sPD-L1 patients with NSCLC [ 123 ], whereas other studies indicated that plasma sPD-L1 (and sPD-L1/sPD-1 ratio) can be positively correlated with overall survival of NSCLC patients [ 126 ]. In parallel, other investigations concluded that exoPD-L1, but not sPD-L1, can be correlated with NSCLC disease progression [ 187 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, overall, the results are contrasted, and sPD-L1 alone does not appears as a sufficiently robust and reliable biomarker to predict outcome in most cases. In NSCLC, for example, some studies underlined that there is no difference in survival outcomes between low sPD-L1 and high sPD-L1 patients with NSCLC [ 123 ], whereas other studies indicated that plasma sPD-L1 (and sPD-L1/sPD-1 ratio) can be positively correlated with overall survival of NSCLC patients [ 126 ]. In parallel, other investigations concluded that exoPD-L1, but not sPD-L1, can be correlated with NSCLC disease progression [ 187 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even in a defined cancer type and with a comparable method (ELISA), large differences of sPD-L1 levels have been reported, complicating the comparisons. For examples, in locally advanced non-small cell lung cancer (NSCLC), a median serum sPD-L1 concentration of 67–68 pg/mL has been reported [ 66 , 122 ], whereas other studies indicated median sPD-L1 levels of 27 pg/mL [ 123 ], 84 pg/mL [ 124 ] and 176 pg/mL [ 125 ]. Moreover, much higher values have been reported with other methods, up to 568 pg/mL measured using a multiplex assay [ 67 ] and 3.84 ng/mL measured with another ELISA procedure [ 126 ].…”
Section: Significance Of Soluble Pd-l1 In Cancermentioning
confidence: 99%
“…In lung cancer, high levels of PDL1 are associated with poor prognosis, shorter OS and the presence of abdominal metastasis [ 16 , 30 ]. More recently, soluble PDL1 serum concentration has been associated with a high metabolic tumor burden, suggesting that the levels of PDL1 may reflect the expansion of tumor volume and tumor lysis during ICI treatment [ 31 ]. More discussed is the role of PD1 as a soluble form.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, despite the more effective way of assessing the [ 18 F]FDG PET-based response in patients treated with ICPIs, available studies suggest that [ 18 F]FDG PET can support decision-making about the continuation/discontinuation of therapy, as it can open several windows able to capture different aspects associated with the effect of treatment (i.e., pseudoprogression, hyperprogression, and IRAE) [56]. Table 2 reports the characteristics of published studies involving the use of [ 18 F]FDG PET to assess the response to ICI [46][47][48]50,51,54,[57][58][59][60][61][62][63][64][65][66][67][68]. Figure 2 shows a representative example of baseline and post-treatment [ 18 F]FDG PET in a patient with advanced NSCLC treated with Nivolumab.…”
Section: Pet-based Response To Icpis In Patients With Nsclcmentioning
confidence: 99%
“…[ 68 Ga]DOTA-conjugate peptides (DOTA-TATE, DOTA-TOC, and DOTA-NOC) PET/CT are used to determine SSTR status (patients with SSTR-positive tumors are more likely to respond to targeted somatostatin analogue therapy), to predict therapeutic response to peptide receptor radionuclide therapy (PRRT) and to monitor the response to PRRT [80]. PRRT is successfully used to target metastatic or inoperable neuroendocrine tumors expressing subtype 2, leading to a longer survival and improved quality of life [81,82].…”
Section: [68 Ga]dota-conjugate Peptidesmentioning
confidence: 99%